Nurturing Student Growth and Empowerment through a Poetry-Rich Classroom - Maspul, Kurniawan Arif (Eduscape : Journal of Education Insight, 2024)
This enthralling exploration digs into the transforming influence of a poetry-rich classroom, revealing a plethora of advantages that educators may use to support student growth and empowerment. Students are given a dynamic platform for creative expression, intellectual advancement, and profound self-discovery when poetry is integrated into the educational environment. Students gain linguistic competence, critical thinking abilities, empathy, cultural understanding, and self-confidence through poetry. The structured poetry writing workshop method emerges as a catalyst for active engagement and growth, helping students through the creation of their own poems. Furthermore, the use of multimedia projects, collaborative initiatives, contests, anthologies, and digital platforms expands and improves student participation and experiences. A poetry-rich classroom is acknowledged for its importance in empowering students as writers, encouraging their personal growth, and establishing a lifetime love of the written word. This study encourages educators to embrace the transforming power of a poetry-rich classroom, fostering an inclusive and vibrant learning atmosphere in which students can thrive as writers and persons.